Curso Jesuíta Conimbricense: Comentário ao 'De Anima' de Aristóteles. - Camps, Maria da Conceição; de Carvalho, Mário Santiago; Miranda, Margarida (Coimbra University Press, 2026)
A Commentary on Aristotle's 'De Anima' as part of the Coimbra Jesuit Course (1592-1606). This volume is dedicated to the translation, edition, explanation (explanatio) and questioning (quaestio) of book III of this Aristotelian work, mostly dealing with biology, the senses, the sensible and intelligible knowledge.